[Alfréd Ruby 12]
1973 to Siófok with trabant water towe, swimming, playing chess, children drawing on the street, 1974 Zsámbék horse-show, wine-tasting, 1972 travel in the country with trabant, Orosháza Szentes Csongrád, 1974 Leipzig, Orient-express on the train, I n the town day&night, 1974 Siófok